Comparing different kidney stone scoring systems for predicting percutaneous nephrolithotomy outcomes: A multicenter retrospective cohort study. (September 2020) - Lai, Shicong; Jiao, Binbin; Jiang, Zhaoqiang; Liu, Jianyong; Seery, Samuel; Chen, Xin; Jin, Bin; Ma, Xiaomeng; Liu, Ming; Wang, Jianye
Abstract: Objective: To compare the predictive performance of five previously described scoring systems (i.e., S.T.O.N.E., Guy's, Clinical Research Office of the Endourological Society (CROES), the Seoul National University Renal Stone Complexity (S-RESC) and the new Stone Kidney Size (SKS) score) for postoperative outcomes regarding stone-free rate (SFR) and complications in adult patients. Methods: Data from 349 patients who underwent percutaneous nephrolithotomy (PCNL) in three urology departments were analyzed. SKS, S.T.O.N.E., S-ReSC, CROES and Guy's nephrolithometry scoring systems were used to retrospectively calculate predictions for each patient. Univariate and multivariate analyses were performed to evaluate factors associated with SFR and complication rates. Receiver operating characteristic (ROC) curves were generated and areas under curves (AUC) were compared to identify the method with the highest predictive value. Results: Median SKS, S.T.O.N.E., S-ReSC, CROES and Guy's scores were 4, 7, 3, 170.8 and 2, respectively. Overall, SFR was 67.0% (234/349) with a complications rate of 36.7% (128/349). AUCs of each method for predicting stone-free status, highlighted reasonable predictive capabilities with 0.709, 0.806, 0 0.869, 0.207, and 0.735, respectively; however, the S-ReSC scoring system had the best discriminative performance. According to multivariate logistic regression and AUC results, none were effectively capable of predicting complications. Conclusions: All scoring systems correlated significantly with stone-free status; although, S-ReSC appears to have the greatest predictive ability. This method is also relatively easy to implement and highly reproducible. However, none of the methods analyzed are able to accurately predict postoperative complications. Highlights: S-ReSC scoring system has the greatest predictive ability for stone-free status. S-ReSC scoring system is also relatively easy to implement and highly reproducible. None of these methods are able to predict the complications effectively.